How Religion Promotes Forgiveness: The Case of Turkish Muslims - AYTEN, ALİ (SAGE PUBLICATIONS LTD, 2012)
Due to developments in positive psychology, the theme of forgiveness has increasingly been observed in psychological studies in recent years. Forgiveness has now become one of positive psychology's favourite topics. It is conceived as an element of religiosity and hence studies focus on the relation between forgiveness and religiosity. This study is carried out to determine the relation between the propensity to forgive and socio-demographic variables (gender and age) and religiosity in the case of the Turkish-Muslim sample. Furthermore, this article aims to describe the relation between forgiveness, humility and pride. In order to investigate these relations, the Interpersonal Forgiveness Scale and Brief Islamic Religiosity Measure have been developed and applied to a sample of 321 people from different parts of Istanbul, Turkey. The findings show that religiosity is positively related to the propensity to forgive and negatively related to feelings of revenge. Furthermore, forgiveness is correlated positively with humility and negatively with pride.
Keywords: interpersonal forgiveness; religiosity; revenge; pride; hopefulness; reconciliation; SELF-FORGIVENESS; PERSONALITY; ADOLESCENTS; MODEL; GOD